Pelatihan Pemasaran Produk Melalui Instagram Di Kelurahan Pasar Bengkulu - Handoko Hadiyanto; Azansyah; Yusnida (Kreativasi : Journal of Community Empowerment, 2022)
Internet use in Indonesia is increasing from time to time. The online marketplace provides convenience for businesses to expand their product market more cheaply and effectively. The Pasar Bengkulu Village does not have any shopping complexes or markets with permanent, semi-permanent or non-building buildings. So this is a problem for the residents of the Pasar Bengkulu Village because of market constraints to market their products. To sell their products on the market will require additional costs for transportation thereby reducing potential income. Therefore, this community service activity aims to provide a better understanding for the people of Pasar Bengkulu Village regarding the optimal use of Instagram to increase business income.